Coaker and the FPU - Memorial University of Newfoundland. Extension Service (Memorial University of Newfoundland. Extension Service, 1970)
An interview with Aaron Bailey, a Newfoundlander who lived in the time of Sir William Coaker and the Fishermen's Protective Union, about their role in the island's history. Date from 10:38 when a production board appears briefly. Incomplete. Lacks credits. Distortion throughout, including moments when the tape was recorded over for a few seconds. There are also poorly filmed shots and moments when audio is present with no picture.